2022
DOI: 10.24127/pj.v11i2.3564
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Online Communication of the Learning Management System for Students’ Writing Ability

Abstract: The use of the Internet is one of the solutions to tackle the communication problems during the covid-19 pandemic. Online activity, which can be done to facilitate learning a language, especially English, is preferable to be synchronous and asynchronous online communication. This research focuses on using asynchronous online communication of the learning management system to enhance students' writing ability in pre-intermediate writing subjects during the covid-19 pandemic. The method of the research is a quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…These findings align with a previous study investigating the effect of LMS as a learning platform on EFL students' learning outcomes. Sholihah (2022), for instance, found the significant effect of the LMS on students' writing skill ability. Similarly, a qualitative study conducted by (Putri & Sari, 2020a) found the impact of using LMS on students' improvement in four English skills.…”
Section: Discussionmentioning
confidence: 97%
“…These findings align with a previous study investigating the effect of LMS as a learning platform on EFL students' learning outcomes. Sholihah (2022), for instance, found the significant effect of the LMS on students' writing skill ability. Similarly, a qualitative study conducted by (Putri & Sari, 2020a) found the impact of using LMS on students' improvement in four English skills.…”
Section: Discussionmentioning
confidence: 97%